Psychometric properties of the Persian version of Proactive-Safety Role Orientation questionnaire (PRO-SAFE) - Reza Jafari Nodoushan; Gholam Hossein Halvani; Reyhane Sefidkar; Hamidreza Mokarami; Mahdi Jafari Nodoushan (BMC Psychology, 2023)
Abstract Background Participation and initiative of workers are effective in promoting safety in the workplace. Proactive-Safety Role Orientation questionnaire (PRO-SAFE) is a proper tool to evaluate the psychological drivers that support the proactive orientation of individuals toward workplace safety. This study was conducted to translate and measure the psychometric properties of the Persian version of PRO-SAFE. Methods The PRO-SAFE was translated into Persian using procedures for translation and cross-cultural adaptation. To collect data, 252 employees of a steel complex were selected. To measure the validity of the questionnaire, face, content, convergent, and construct validity was utilized. The questionnaire’s reliability was evaluated by assessing its internal consistency. Results The mean of the content validity index and content validity ratio was equal to 0.83 and 0.85, respectively. We found a positive correlation between PRO-SAFE and safety behavior dimensions (r = 0.372 to 0.792, P < 0.001). Confirmatory factor analysis showed the Persian version of the PRO-SAFE questionnaire had an excellent six-factor model consistent with the original questionnaire. Cronbach’s alpha of the Persian version of the PRO-SAFE questionnaire was obtained between 0.717 to 0.880. Conclusions The Persian version of the PRO-SAFE questionnaire was found to have appropriate psychometric properties, indicating that it can be confidently used as a valid tool for assessing proactive role orientation toward safety management among Iranian employees.